Concise or comprehensive? Predictors of impact assessment choices for electric transmission line projects. Issue 5 (20th June 2022) - Scott, Ryan P.; Ulibarri, Nicola; Scott, Tyler A.
Abstract: Environmental impact assessment (EIA) procedures required in the United States and many other countries are often highlighted as a major hindrance to timely and efficient deployment of critical infrastructure projects. Under the U.S. National Environmental Policy Act, a more extensive environmental impact statement (EIS) review can take several more years and cost much more than a succinct environmental assessment (EA). This not only affects the project in question, but also likely informs how—or whether—additional projects are pursued. Thus, understanding key predictors of the EA versus EIS choice sheds light on supply‐side considerations affecting infrastructure deficits. Using the case of NEPA reviews conducted for 244 transmission line projects between 2005 and 2018 by two U.S. federal agencies in the western United States, the Bureau of Land Management (BLM) and Department of Energy (DOE), this addresses the following question: What project features most predict whether EA or an EIS is used to assess a transmission line project? Drawing upon NEPA assessment guidance and agency NEPA records, we use a regression classification tree to analyze how protocols and project attributes relate to assessment choice. The result is essentially a null finding: transmission line length is by far the most important predictor of whether a project receives an extensive EIS or a shorter EA, with little predictive value provided by other attributes. While absolute project size undoubtedly influences impacts, the lack of further differentiation in what predicts use of EISs versus EAs suggests assessment does not simply respond to project details but also shapes proposal and design choices beforehand.